Psychological discomfort and binge drinking in Mexican adults - Josué Alai Quiroz-Reyes; Ietza Rocío Bojórquez-Chapela; M Arantxa Colchero (Salud Pública de México, 2022)
Objective. To analyze the relationship between binge drinking and psychological discomfort in Mexican adults. Materials and methods. We used data from the 2011 National Survey on Addictions in Mexico. A two-stage bivariate probit model with instrumental variables was used to address the potential reverse causality in the association between binge drinking and psychological discomfort. Results. Individuals who had at least one episode of binge drinking in the last year and in the last month are more likely to experience psychological discomfort. Conclusion. This study shows the relevance of developing prevention and treatment programs for people who consume alcohol in excess due to its negative effects on mental health.